(untitled) (Northern International Medical College Journal, 2018)
Background : Antenatal care (ANC) is an important determinant of high maternal mortality rate and one of the basic components of maternal care on which the life of mothers and newborn babies depend. Objective : To study the Antenatal care practice among pregnant women in a selected rural area. Methodology : This descriptive cross-sectional study was conducted among pregnant women in a selected rural area from July 2016 to December 2016. Total sample was 121. Purposive sampling technique was followed. Data collection was done by face to face interview by using pretested structured questionnaire. Data was analyzed by SPSS version 17.0. Results : A total of 121 women were interviewed. Sixty nine (57.02%) pregnant women were registered for ANC. Among them 47(68.11%) of respondents completed more than 4ANC visits. For the current pregnancy 56(46.28%) preferred Upazila Health Complex (UHC) and home delivery was preferred by 34(28.09%) respondents. Among the respondent age group 25-30 yrs were 61(50.41%) and educated upto primary level were 59(48.76%). Monthly income between 5000-10000 taka was among 48(39.66%) respondents. Most of their husbands (52.06%) were educated up to primary level and 25.61 % of them were garments worker and 23.96 % were day laborers. Conclusion : ANC practice was not satisfactory. Only half of the pregnant women attended for ANC and completed minimum four visits. Nearly half of the pregnant women preferred UHC. Educated women from lower economic status were found to attend for ANC. Northern International Medical College Journal Vol.10(1) Jul 2018: 339-342